Co-Simulation Interfacing Capabilities in Device-Level Power Electronic Circuit Simulation Tools: An Overview - Wentao Wang; Wenying Yang; Venkata Dinavahi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
Power electronic circuit simulation today has become increasingly more demanding in both the speed and accuracy. Whilst almost every simulator has its own advantages and disadvantages, co-simulations are becoming more prevalent. This paper provides an overview of the co-simulation capabilities of device-level circuit simulators. More specifically, a listing of device-level simulators with their salient features are compared and contrasted. The co-simulation interfaces between several simulation tools are discussed. A case study is presented to demonstrate the co-simulation between a device-level simulator (PSIM) interfacing a system-level simulator (Simulink), and a finite element simulation tool (FLUX). Results demonstrate the necessity and convenience as well as the drawbacks of such a comprehensive simulation.